Development of the Nagham Qur’an - Suarni, Suarni (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Al-Qur'an was revealed by Allah SWT in Arabic, which has a very beautiful language structure. To understand the meaning contained therein, the Qur'an must be read well and correctly. Reading the Qur'an well and correctly is inseparable from the reading rules contained in the science of tajweed. In addition, the Prophet also recommended reading the Qur'an with a good and beautiful voice. Because one of the elements of the perfection of the Qur'an is reading it well and beautifully. In the current context, reading the Qur'an in a good and beautiful way can also be termed nagham Qur'an or known as the art of reading the Qur'an. But in this case, the term is not fully applied by Qur'an readers. This causes some Qur'anic readers to ignore the rules of Qur'anic recitation. Referring to these problems, nagham Qur'an and the history of its development presumably require a special study, with the focus of the study being on the meaning of nagham and the history of its development. The method used in explaining this study is a qualitative method with an analytical, descriptive approach. Based on the focus of the study, the term nagham has the same meaning as talhin and tarannum, namely, reading the Qur'an with a beautiful voice while still applying the rules of tajweed. Reading the Qur'an with nagham began with the Prophet Muhammad and has been carried on by his companions and subsequent generations.